Efektifitas Edukasi Kader Kesehatan Dalam Deteksi Dini dan Skrining Faktor Risiko Tuberkulosis Di Kota Palembang: Effectiveness of Health Cadre Education in Early Detection and Screening of Tuberculosis Risk Factors in Palembang - Maksuk, Maksuk; Amin, Maliha; Hendawati, Hendawati (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Tuberculosis case detection through screening is an effort to control and prevent tuberculosis transmission in the community. Cadres are community members formed to assist in tuberculosis case detection. The activity aims to improve the knowledge, attitudes, and skills of cadres in conducting early detection dan tuberculosis screening. The community service implementation method was through education, targeting 20 health cadres. This activity was conducted from 25 – 30 November 2024 in Kampung Jaya Laksana, Tiga Empat Ulu Village, Palembang City. The pre-experimental activity design used a one-group paired t-test approach. This activity consisted of three stages: preparation, implementation, and evaluation. The results showed that the majority of cadres were aged 51 years or older, had a junior high school education, and had been a cadre for 2 years or more. There was a difference in knowledge, attitudes, and responses before and after the tuberculosis case detection education through screening, with a p-value of 0.005 for each. The conclusion of this activity was that there was an increase in the knowledge, attitudes, and responses of cadres before and after the tuberculosis case detection education through screening. Early detection and regular tuberculosis screening training needs to be conducted for cadres in the community health center work area.